Analisis Yuridis Penebangan Liar (Illegal Logging) dalam Perspektif Hukum Lingkungan Indonesia - Nila Syapitri Hsb; Cucu Robiatul Adawiah; Intan Nuraeni; Teti Saputri; Difky M. N. F. (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes illegal logging from the perspective of Indonesian environmental law, focusing on environmental impacts, economic and social implications, and the effectiveness of law enforcement. The research method used is normative juridical with a conceptual approach and case studies, through an examination of legislation, court decisions, official government reports, and relevant previous studies. The results show that illegal logging contributes significantly to the environmental crisis, including increased carbon emissions, biodiversity degradation, and ecological disasters, while also causing huge losses to the state due to lost revenue from the forestry sector. The implementation of the Forestry Law and the P3H Law has shown progress, particularly in imposing criminal sanctions on perpetrators and corporations, but still faces obstacles in inter-agency coordination and disparity in court rulings. Preventive instruments such as the Timber Legality Verification System and Social Forestry have proven to support improvements in forest governance, although they require policy strengthening and continuous monitoring.